The bathroom key : put an end to incontinence - Kassai, Kathryn (Demos Health, 2012)
"Urinary incontinence is an underdiagnosed and underreported condition with major economic and psychosocial effects on society. Women are more likely to experience it due to issues with the pelvic floor brought on by pregnancy and menopause. The Bathroom Key is a treatment plan for women to cure their own incontinence issues. It also allows women to identify with other women through the anecdotal stories that echo their feelings of isolation and embarrassment. Written in easy-to-understand language, the book is a genuine teaching tool, guiding the reader to a better understanding of her body and effective remedies. Whereas in recent years some mention of the Kegel muscles and exercises have become common knowledge, this book is much more than just Kegels. By incorporating key elements of the physical therapy approach in this book, the reader will be encouraged to self-assess, modify behaviors, re-train her bladder, alter dietary habits, and practice a variety of exercises to self-treat and cure her incontinence. In most cases urinary incontinence is completely treatable with physical therapy. Women can regain bladder control, not have to take medications, throw away pads and regain their dignity"--